A Hybrid Perovskite-Based Electromagnetic Wave Absorber with Enhanced Conduction Loss and Interfacial Polarization through Carbon Sphere Embedding - Xuehua Lian; Yao Yao; Ziming Xiong; Yantao Duan; Jianbao Wang; Shangchen Fu; Yinsuo Dai; Wenke Zhou; Zhi Zhang (Nanomaterials)
Electronic equipment brings great convenience to daily life but also causes a lot of electromagnetic radiation pollution. Therefore, there is an urgent demand for electromagnetic wave-absorbing materials with a low thickness, wide bandwidth, and strong absorption. This work obtained a high-performance electromagnetic wave absorption system by adding conductive carbon spheres (CSs) to the CH3NH3PbI3 (MAPbI3) absorber. In this system, MAPbI3, with strong dipole and relaxation polarization, acts dominant to the wave absorber. The carbon spheres provide a free electron transport channel between MAPbI3 lattices and constructs interfacial polarization loss in MAPbI3/CS. By regulating the content of CSs, we speculate that this increased effective absorption bandwidth and reflection loss intensity are attributed to the conductive channel of the carbon sphere and the interfacial polarization. As a result, when the mass ratio of the carbon sphere is 7.7%, the reflection loss intensity of MAPbI3/CS reaches −54 dB at 12 GHz, the corresponding effective absorption bandwidth is 4 GHz (10.24–14.24 GHz), and the absorber thickness is 2.96 mm. This work proves that enhancing conduction loss and interfacial polarization loss is an effective strategy for regulating the properties of dielectric loss-type absorbing materials. It also indicates that organic-inorganic hybrid perovskites have great potential in the field of electromagnetic wave absorption.